EHealth interventions for the prevention and treatment of overweight and obesity in adults: a systematic review with meta‐analysis. Issue 5 (5th March 2015) - Hutchesson, M. J.; Rollo, M. E.; Krukowski, R.; Ells, L.; Harvey, J.; Morgan, P. J.; Callister, R.; Plotnikoff, R.; Collins, C. E.
Summary A systematic review of randomized controlled trials was conducted to evaluate the effectiveness of eHealth interventions for the prevention and treatment of overweight and obesity in adults. Eight databases were searched for studies published in English from 1995 to 17 September 2014. Eighty‐four studies were included, with 183 intervention arms, of which 76% (n = 139) included an eHealth component. Sixty‐one studies had the primary aim of weight loss, 10 weight loss maintenance, eight weight gain prevention, and five weight loss and maintenance. eHealth interventions were predominantly delivered using the Internet, but also email, text messages, monitoring devices, mobile applications, computer programs, podcasts and personal digital assistants. Forty percent (n = 55) of interventions used more than one type of technology, and 43.2% (n = 60) were delivered solely using eHealth technologies. Meta‐analyses demonstrated significantly greater weight loss (kg) in eHealth weight loss interventions compared with control (MD −2.70 [−3.33, −2.08], P < 0.001) or minimal interventions (MD −1.40 [−1.98, −0.82], P < 0.001), and in eHealth weight loss interventions with extra components or technologies (MD 1.46 [0.80, 2.13], P < 0.001) compared with standard eHealth programmes. The findings support the use of eHealth interventions as a treatment option for obesity, but there is insufficient evidence for the effectiveness of eHealth interventions for weight loss maintenance or weight gain prevention.